The Utilization of Fermented Rice Straw Ammoniation Feed (Amofer ) to Increase Body weight Gain of Bali bull in Batu Kuta Lombok Barat - Abyadul Fitriyah; Ria Harmayani; Aisah Jamili; Yuni Mariani; Ni Made Andry Kartika; Nefi Andriana Fajri; Isyaturriyadhah Isyaturriyadhah (Fakultas Pertanian Universitas Muara Bungo, 2022)
The utilization of rice straw waste as fermented ammonia (Amofer) for cattle farming was done in Desa Batu Kuta Kecamatan Narmada Kabupaten Lombok Barat from April-September 2021 with aims to introduce Amofer feed technology to increase body weight of bulls. The research procedures that have been carried out includes: 1). Amofer feed manufacture by adding ammonia in rice straw (Ammonia Straw), and 2). Amofer feeding management. This study was used 15 Bali bulls with 225 kg – 250 kg of body weights. There are three (3) treatments of Amofer feeding management, namely: R0 = Farmer's treatment (straw+concentrate); R1 = Forage 30% (15% elephant grass + 15% gamal grass) + 69 % Amofer feed + 1 % Concentrate (corn + bran); R2 = Forage 70% (35% elephant grass + 35% gamal grass) + 29 % Amofer feed + 1 % Concentrate (corn + bran). Parameters measured were feed consumption (FC) and daily body weight gain (DBWG). The results showed that the highest of FC was found on Bali bull with R-2 treatment (14.42 kg/each/day), and the highest of DBWG was shown by Bali bull whith R-2 treatment (0.66 kg/each/day). It is concluded, the Amofer feed formula in R2 treatment was more efficiently applied to ruminants with the aim of fattening cattle.